Prophetic Hadith and the Spectrum of Night Devotion: Reconstructing Qiyām al-Lail in Contemporary Context - Kade, Samsuddin; Johariyah, St; Ahmad, Arifuddin; Kara, Siti Aisyah; Puyu, Darsul S (Prodi Ilmu Hadis Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2025)
The concept of qiyām al-lail in Islamic tradition is often narrowly interpreted as night prayers such as tahajjud or witir. However, numerous Prophetic traditions indicate that nighttime devotion includes not only prayer but also spiritually significant acts like remembrance (dhikr), Qur’anic recitation, consultation, education, and social service. This study aims to reinterpret the meaning of qiyām al-lail in the Prophet’s ḥadīths through a ma’ānī al-ḥadīth approach that emphasizes textual, intertextual, and contextual analysis. The method employed is qualitative library research with takhrīj al-ḥadīth and critical analysis of the chains of transmission (isnād) and content (matn) of ḥadīths found in the kutub al-tis’ah. The results show that the examined ḥadīths are authentic, free from ‘illah or shudhūdh, and provide a robust basis for reinterpretation. Through a meaning-based lens, qiyām al-lail encompasses not only ritual practices like prayer but also other nightly acts of devotion intended for seeking nearness to Allah. This reinterpretation affirms that spiritual excellence at night can manifest in various forms of contextualized religious and social engagement. Thus, this study expands the understanding of nighttime worship and brings the prophetic tradition closer to the lived realities of contemporary Muslims